An approach to the term quality in superior education - Carrasco Loyola, Milagros (2015)
One of the most difficult tasks is to define quality. The term has been evolution over the last century to the present. There is no consensus for its conceptualization; however it has been a constant search for diverse organizations and more recently, in the field of education. The emphasis on quality in superior education demands a revision of its definition among different stakeholders from academia to improve educational processes. The measurement of quality is another aspect that deserves attention by the diversity of approaches and therefore difficult to define the parameters for evaluation. The evaluation of educational quality can be internal when the institution evaluates your processes academic or related to these, and on the other hand, the external evaluation that allows access to the accreditation of the degree program or institution as recognition of the quality. Various international quality models coincide in the aspects that should be evaluated in the institutions: Educational Project, Students, Teachers, Academic Processes, Research, National and International Visibility, Graduated, Institutional well-being, Organization, Administration and Management, Physical and Financial Resources The Peruvian model accreditation is based on a process approach initially applied to the business and work of the Peruvian university adapt to changes in demand for raising educational quality.